LOCAL TOURISM MARKETS IN ITALY - AN ECONOMETRIC ANALYSIS AND POLICY PROPOSALS - Gianluigi Coppola; Teresa Vanacore (European Regional Science Association (ERSA), 2005)
Tourism is very important in Italy. In this article we will discuss about the Economy of the Italian Local Labour Markets specialized in Tourism. We will try to explain, through statistical analysis applied to an Econometrical model, the differences existing among them. The result of our research is that the dichotomy of the Italian economy – North vs. South – is also present in the Tourism industry. Nevertheless, there are significant differences among the Tourism Local Markets in Southern Italy. This implies that a policy on local development may help the region to grow.
Keywords: 330